2005
DOI: 10.1107/s0108767305091956
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of murine 11β-hydroxysteroid dehydrogenase 1: an important therapeutic target for diabetes

Abstract: Precursors for isoprenoid synthesis are essential in all organisms. These compounds are synthesized by one of two known routes: the well characterized mevalonate pathway [1] or a recently discovered non-mevalonate route which is used in many bacteria and human pathogens [2]. Since the second pathway is both vital and unlike any found in humans, enzymes catalysing reactions along this synthetic route are possible drug targets. The structure of one such enzyme from the thermophilic bacterium Thermus thermophilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Attempts to express the active-site mutant K187N in the human F278E background also resulted in a protein that would not express in a soluble form in the recombinant E. coli system. Because the K187 residue is known to be involved in cofactor binding, 14,20,24,28 these results again suggest that the interaction with NADP(H) is required for correct folding and stability, at least in E. coli. This is supported by the observation that high-level expression of human 11b-HSD1 in a soluble form in bacteria requires addition of an inhibitor compound, 36 for example, the steroid analogue carbenoxolone used in these studies, which also presumably requires prior cofactor binding.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Attempts to express the active-site mutant K187N in the human F278E background also resulted in a protein that would not express in a soluble form in the recombinant E. coli system. Because the K187 residue is known to be involved in cofactor binding, 14,20,24,28 these results again suggest that the interaction with NADP(H) is required for correct folding and stability, at least in E. coli. This is supported by the observation that high-level expression of human 11b-HSD1 in a soluble form in bacteria requires addition of an inhibitor compound, 36 for example, the steroid analogue carbenoxolone used in these studies, which also presumably requires prior cofactor binding.…”
Section: Discussionmentioning
confidence: 59%
“…Crystals were grown as per Materials and Methods with the data collection and refinements statistics given in Table III. Each monomer in the guinea pig F278E structure had the same overall Rossman fold as the other published 11b-HSD1 structures 14,24,28 and had a quaternary assembly of a tetramer made up of a dimer-of-dimers [ Fig. 6(A)].…”
Section: Crystal Structure Of Guinea Pig F278ementioning
confidence: 94%
“…11β-HSD1 is a dimeric enzyme, and although a mutant K187N homodimer would be expected to be inactive, the effect of heterodimer formation between WT and mutant subunits (as could occur in heterozygous humans, such as case B) was uncertain. The two subunits of 11β-HSD1 are closely intertwined, facilitating a close structural interplay between the monomers (4,5). Thus, the K187N mutation in one subunit possibly could negatively affect the activity of an adjacent WT subunit.…”
Section: Discussionmentioning
confidence: 99%
“…11β-HSD1 is a member of the short-chain dehydrogenase reductase (SDR) superfamily of enzymes and naturally exists as a homodimer (2)(3)(4)(5), although some studies have suggested that it also may function as a homotetramer (6). Unusually for an SDR enzyme, 11β-HSD1 has an N-terminal membrane anchor (7,8), with a small portion of the N-terminal segment of the enzyme present in the cytosol.…”
mentioning
confidence: 99%
See 1 more Smart Citation